A COMPARATIVE ANALYSIS OF GENDERED LANGUAGE FEATURES: THE MALE AND FEMALE PROTAGONISTS IN FRUITS BASKET - Syuhra, Marsha Aqillah Putri (jfpublisher, 2023)
This study presents a comparative analysis of gendered language features as exhibited by the male and female protagonists in the anime series Fruits Basket (Season 1). Grounded in Deborah Tannen’s (1990) sociolinguistic framework, which posits that male and female communication styles often reflect contrasting cultures, a “report talk” prioritizing status and independence versus a